Studies on the Lithium Ion Diffusion Coefficients of Electrospun Nb2O5 Nanostructures Using Galvanostatic Intermittent Titration and Electrochemical Impedance Spectroscopy - Rajan, Jose; Reddy, M. Venkatashamy; Le Viet, Anh; Ozoemenad, Kenneth I; Chowdary, B. V. R; Ramakrishna, S. (Elsevier, 2014)
We have studied the Li-diffusion coefficient values of electrospun Nb2O5 nanofibers and nanonuggets for lithium batteries. In brief, Nb2O5 nanofibers were prepared by electrospinning followed by sintering at temperatures range 500–1100 °C for 1 h in air to obtain pseudo-hexagonal, orthorhombic (O), and monoclinic (M) Nb2O5 phases. Electrochemical properties were evaluated by galvanostatic technique at room temperature. The H-, O- and M-Nb2O5 polymorphs delivered discharge capacities (at second cycle) of 152, 189 and 242 (±5) mA h g−1, respectively. The lithium diffusion coefficients (DLi) are calculated using galvanostatic intermittent titration technique (GITT) and electrochemical impedance spectroscopy (EIS) techniques carried at room temperature. The evaluated DLi values by GITT for H-, O-, and M-Nb2O5 phases are in the range 10−17–10−16, 10−15–10−14, and 10−13–10−12 cm2 s−1, respectively, in the voltage range 1.0–2.6 V vs. Li. DLi evaluated by EIS gave similar trend in the values but with a difference of one order higher magnitude.